5R Education for Micro, Small, and Medium Enterprises (MSMEs) in Sukaharja Village - Fachmi Al Faroqi; Purnama Wijaya (Yayasan Daarul Huda Kruengmane, 2026)
This Community Service activity aims to provide education and assistance in implementing the 5R work culture (Sort, Set in Order, Shine, Standardize, and Sustain) to Micro, Small, and Medium Enterprises (MSMEs) in Sukaharja Village, Tangerang Regency. MSMEs are an important sector in supporting the rural economy; however, in practice, many MSME actors have not yet implemented organized and sustainable workplace management. Common problems identified include the accumulation of unnecessary items, inefficient arrangement of work equipment, inconsistent maintenance of workplace cleanliness, and low work discipline. These conditions have an impact on low productivity, increased risk of workplace accidents, and decreased product quality. Through this 5R education activity, it is expected that MSME actors will be able to understand and implement more organized, clean, and disciplined work principles, thereby improving work efficiency, safety, and business competitiveness in a sustainable manner.